1997
DOI: 10.1074/jbc.272.40.24961
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-induced Desensitization of the μ Opioid Receptor Is Determined by Threonine 394 Preceded by Acidic Amino Acids in the COOH-terminal Tail

Abstract: To identify the structural determinants necessary for opioid receptor desensitization, we serially ablated potential phosphorylation sites in the carboxyl tail of the receptor and examined their effects on [D-Ala 2 ,N-MePhe 4 ,Gly-ol 5 ]enkephalin (DAMGO)-induced desensitization. First, we replaced Thr 394 with alanine (T394A) and stably expressed this mutant receptor in Chinese hamster ovary cells. The T394A receptor did not desensitize after 1 h of treatment with DAMGO, indicating that Thr 394 is required fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
73
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 29 publications
5
73
2
Order By: Relevance
“…Like them, we found no phosphorylated residue in the last 16 residues of the MOP C-tail, thus confirming that Thr-396 (Thr-394 in rodent) is not phosphorylated under basal conditions and after DAMGO (or 1DMe) treatment, contrary to what was suggested by indirect studies (68). In agreement with previous studies (38,50), we found that Ser-365 (Ser-363 in rodent), the main site of MOP receptor phosphorylation by PKC when the kinase is directly activated by phorbol ester (69), was phosphorylated under basal conditions and not affected by DAMGO treatment nor by 1DMe treatment.…”
Section: Discussioncontrasting
confidence: 56%
“…Like them, we found no phosphorylated residue in the last 16 residues of the MOP C-tail, thus confirming that Thr-396 (Thr-394 in rodent) is not phosphorylated under basal conditions and after DAMGO (or 1DMe) treatment, contrary to what was suggested by indirect studies (68). In agreement with previous studies (38,50), we found that Ser-365 (Ser-363 in rodent), the main site of MOP receptor phosphorylation by PKC when the kinase is directly activated by phorbol ester (69), was phosphorylated under basal conditions and not affected by DAMGO treatment nor by 1DMe treatment.…”
Section: Discussioncontrasting
confidence: 56%
“…More specifically, segments of the carboxyl tail and specific residues contained therein have been identified for both (20,23,24) and ␦ (25) receptors as important for agonist-induced internalization. We hypothesized therefore, that the inability of the ␦ receptor to internalize when co-expressed with the receptor indicated that the relevant region of the carboxyl tail that mediated ␦ opioid receptor internalization was somehow occluded.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, several Ser/Thr residues within the COOH terminus of opioid receptors have been suggested to be involved in the regulation of these receptors. Thr 394 , Ser 353 , and Ser 369 have been shown to be important for the regulation of -opioid receptors (20,34,35), ␦-opioid receptors (18,19), and -opioid receptors (36), respectively, although phosphorylation of these residues has not been determined. Recently, a T394A mutation was shown to significantly block DAMGO-induced MOR phosphorylation to approximately 10% of the wild type receptor and impair receptor desensitization in Chinese hamster ovary cells (37), indicating that this residue is a phosphorylation site.…”
Section: Discussionmentioning
confidence: 99%
“…Several kinases have been postulated to be involved in opioid receptor phosphorylation including protein kinase A (38,39), protein kinase C (33,40), GRKs (25,34), mitogen-activated protein kinase (41,42), calmodulin kinase II (43,44), and tyrosine kinase (32 (21). Although MOR and DOR have differences in their C-tail primary sequence, it is interesting to note that a common motif encompassing agonistinduced phosphorylated sites exists for both receptor subtypes.…”
Section: Discussionmentioning
confidence: 99%